Medium and high-entropy high-temperature giant dielectric ceramic material as well as preparation method and application thereof
By adopting the composition of medium and high entropy high temperature giant dielectric ceramic materials, the problem of poor dielectric performance in high temperature environments is solved, and the performance of high dielectric constant, low loss and wide temperature zone is achieved Improved, suitable for high-temperature capacitor applications.
Patent Information
- Application Number
- CN202411605727.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional dielectric ceramic materials exhibit low dielectric constant, excessive loss and narrow use temperature zone in high temperature environments, making it difficult to meet the application needs of modern electronic components under high performance and high temperature conditions.
Using the composition formula (1-x)[(Bi0.5Na0.5)0.85K0.1A0.1]TiO3-xBi(B1B2)0.5O3 of medium and high entropy high temperature giant dielectric ceramic materials, it is composed of non-equimolar elements. The solid solution is formed with the introduction of stable phases, accurately regulating the configuration entropy of the material, thereby improving dielectric properties.
The performance of giant dielectric materials with high dielectric constant and low dielectric loss under high temperature conditions is achieved, and the temperature range and frequency band of materials are expanded, which is suitable for the preparation of high-temperature capacitors.
Smart Images

Figure CN119462131A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of dielectric ceramic materials, and in particular relates to a medium- and high-entropy high-temperature giant dielectric ceramic material and a preparation method and application thereof. Background Art
[0002] As a key material for preparing basic components in the electronics industry, dielectric ceramic materials are widely used in modern power electronics industry, national defense weapons and equipment, aerospace, rail transportation and other fields. In recent years, with the rapid development of electronic information technology, the demand for miniaturized, intelligent, multifunctional, highly integrated and high-performance electronic components has continued to increase, and a large number of electronic components need to be used in high-temperature environments. Traditional dielectric ceramic materials have problems such as low dielectric constant, excessive loss, and narrow operating temperature range. It is difficult to meet the trend of miniaturization and high integration of electronic components and the requirements of sustainable application under high temperature conditions.
[0003] "Entropy engineering" is a new material design concept that gives materials a new structure and a variety of excellent physical properties through the regulation of configurational entropy. The high entropy of materials can suppress impurities, stabilize the phase structure and further improve the mechanical properties, thermal properties, catalytic properties and dielectric properties of the materials. As a new type of material evolved from high entropy alloys, high entropy ceramics are usually composed of five or more main elements in equal molar ratios. Due to the fixed ratio of the constituent elements, their configurational entropy and performance regulation range are limited. Therefore, it is necessary to develop medium and high entropy oxides composed of elements with non-equimolar ratios, introduce other stable phases to form solid solutions on this basis, and accurately regulate the configurational entropy of the material by controlling the changes in the introduced phase content, thereby realizing a new system of giant dielectric materials that can be sustainably applied under high temperature conditions. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a medium- and high-entropy high-temperature giant dielectric ceramic material with a high dielectric constant working in a high temperature region and a preparation method thereof. The high-temperature giant dielectric ceramic material is used for the preparation of high-temperature capacitors.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a medium- and high-entropy high-temperature giant dielectric ceramic material, the composition formula of the medium- and high-entropy high-temperature giant dielectric ceramic material is: (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 O3; wherein: 0≤x≤0.15, A is Ba, B1 is Mg, and B2 is Zr.
[0006] The present invention also provides a method for preparing the above-mentioned medium and high entropy high temperature giant dielectric ceramic materials, the method comprising:
[0007] S1. According to the chemical composition of medium and high entropy high temperature giant dielectric ceramic materials (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 O3 selecting initial raw material powders and drying them to obtain dried initial raw material powders;
[0008] S2, the dried initial raw material powder obtained in S1 is treated according to (1-x)[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 The raw materials are mixed in a stoichiometric ratio of 1,2-dihydrogen 2-nitrogen (2-nitrogen) and 1,4-dihydrogen 2-nitrogen (2-nitrogen) (2-nitrogen) (3-nitrogen) (4-nitrogen) (5-nitrogen) (6-nitrogen) (7-nitrogen) (8-nitrogen) (9-nitrogen) (10-100-110-120-130-140-260-280-300-360-38 ...
[0009] S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder;
[0010] The pre-sintering method comprises: heating from room temperature to 800°C to 980°C at a heating rate of 2°C / min to 8°C / min, pre-sintering at a constant temperature for 1h to 4h, and naturally cooling to room temperature to obtain pre-sintered powder;
[0011] S4, adding agate balls and deionized water to the pre-burned powder obtained in S3, ball milling at a speed of 300r / min-800r / min for 2h-10h, separating the agate balls, drying at a temperature of 120°C-250°C for 8h-48h, and passing through a 100-mesh sieve to a 230-mesh sieve after grinding to obtain a pre-burned powder after ball milling;
[0012] S5, adding a polyvinyl alcohol aqueous solution with a mass fraction of 3% to 8% to the pre-sintered powder after ball grinding obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body;
[0013] S6. Sintering the ceramic green body obtained in S5 to obtain medium- and high-entropy high-temperature giant dielectric ceramic materials.
[0014] Preferably, the raw material powders containing K and Na in the initial raw material powders in S1 are carbonates corresponding to the elements, the raw material powders containing A are carbonates corresponding to the elements, and the raw material powders containing Bi, Ti, B1, and B2 are oxides corresponding to the elements.
[0015] Preferably, the mass of the agate balls in the ingredients in S2 is in the ratio of diameter 10mm:5mm:2mm=(3-4):(2-3):1; the mass ratio of the dried initial raw material powder, agate balls and deionized water is 1:(1.5-2):(2-4).
[0016] Preferably, the mass of the agate balls in S4 is in the ratio of diameter 10 mm: 5 mm: 2 mm = (3-4): (2-3): 1; the mass ratio of the pre-burned powder, agate balls and deionized water is 1: (1.5-2): (2-3).
[0017] Preferably, the tabletting method in S5 is: maintaining the pressure for 10s to 60s under a unidirectional pressure condition of 100MPa to 350MPa.
[0018] Preferably, the mass ratio of the polyvinyl alcohol aqueous solution with a mass fraction of 3% to 8% in S5 to the pre-burnt powder after ball grinding is (5% to 12%):1.
[0019] Preferably, the sintering method in S6 is: heating from room temperature to 500°C to 600°C at a heating rate of 1.5°C / min to 3°C / min, keeping warm for 1h to 3h, then heating to 1000°C to 1200°C at a heating rate of 3°C / min to 9°C / min, sintering at a constant temperature in air for 1h to 4h, and then cooling to room temperature at a cooling rate of 5°C / min to 9°C / min.
[0020] Preferably, the medium and high entropy high temperature giant dielectric ceramic materials in S6 have a dielectric constant of >10 in the temperature range of 89°C to 350°C and the frequency range of 100Hz to 500Hz. 5 .
[0021] The present invention also provides the application of medium- and high-entropy high-temperature giant dielectric ceramic materials prepared by the above method, and the medium- and high-entropy high-temperature giant dielectric ceramic materials are used for the preparation of high-temperature capacitors.
[0022] The medium and high entropy high temperature giant dielectric ceramic material composition formula (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5In O3, it can also be: 0≤x<0.2, A is any one of Ba, Sr, Ca, B1 B2 is any one of Mg, Zn, Fe and any one of Zr, Hf, Sn in combination, all of which can be prepared into medium- and high-entropy high-temperature giant dielectric ceramic materials for high-temperature capacitors.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. The medium and high entropy high temperature giant dielectric ceramic materials provided by the present invention break the conventional molecular configuration of high entropy oxides with equal molar ratios. On the one hand, non-equimolar ratio elements are used, and on the other hand, other stable phases are introduced to form solid solutions. The configuration entropy of the dielectric ceramic material is precisely controlled by controlling the introduced phase content and the ratio of non-equimolar ratio elements.
[0025] 2. The configuration entropy of the giant dielectric ceramic material provided by the present invention belongs to the medium entropy and high entropy range, realizing a new system of medium and high entropy giant dielectric materials that can be sustainably applied under high temperature conditions.
[0026] 3. The medium and high entropy high temperature giant dielectric ceramic materials provided by the present invention can achieve dielectric constants > 10 in the temperature range of 89-350°C and the frequency range of 100-500Hz. 5 , can be used as a high temperature capacitor.
[0027] 4. The medium and high entropy high-temperature giant dielectric ceramic materials provided by the technical solution of the present invention are sintered at normal pressure in air, and the preparation process is simple, which is conducive to industrial production and application.
[0028] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The medium and high entropy high temperature giant dielectric (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-xBi(MgZr) 0.5 Entropy value and tolerance factor of O3 ceramic materials.
[0030] Figure 2 It is the XRD diagram of the medium and high entropy high temperature giant dielectric ceramic materials in Examples 1-4 of the present invention.
[0031] Figure 3 It is a SEM scan of the medium and high entropy high temperature giant dielectric ceramic materials in Examples 1-4 of the present invention.
[0032] Figure 4The medium-entropy high-temperature giant dielectric [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]Image of the dielectric properties of TiO3 ceramic materials changing with temperature.
[0033] Figure 5 The medium entropy high temperature giant dielectric 0.95[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.05Bi(MgZr) 0.5 A graph showing how the dielectric properties of O3 ceramic materials change with temperature.
[0034] Figure 6 It is the high entropy high temperature giant dielectric 0.90[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.10Bi(MgZr) 0.5 A graph showing how the dielectric properties of O3 ceramic materials change with temperature.
[0035] Figure 7 It is the high entropy high temperature giant dielectric 0.85[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.15Bi(MgZr) 0.5 A graph showing how the dielectric properties of O3 ceramic materials change with temperature. DETAILED DESCRIPTION
[0036] Example 1
[0037] The composition formula of the medium-entropy high-temperature giant dielectric ceramic material of this embodiment is [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3.
[0038] A method for preparing the above medium-entropy high-temperature giant dielectric ceramic material, the method comprising:
[0039] S1. According to the chemical composition of medium-entropy high-temperature giant dielectric ceramic materials [(Bi 0.5 Na 0.5 ) 0.85 K0.1 Ba 0.1 ]TiO3 selects initial raw material powders and dries them to obtain dried initial raw material powders;
[0040] That is, the Na2CO3 raw material powder, Bi2O3 raw material powder, K2CO3 powder and BaCO3 raw material powder are dried at 300°C for 6 hours respectively; the selected TiO2 raw material powder is dried at 900°C for 4 hours;
[0041] The purity of the Na2CO3 raw material is 99.8%, the purity of the Bi2O3 raw material is 99%, the purity of the K2CO3 raw material is 99%, the purity of the BaCO3 raw material is 99%, and the purity of the TiO2 raw material is 98%;
[0042] S2, the dried Na2CO3 powder, Bi2O3 powder, K2CO3 powder, BaCO3 powder and TiO2 raw materials in S1 are prepared according to [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3 is prepared in a stoichiometric ratio, agate balls and deionized water are added, ball milling is performed at a speed of 300r / min for 12h, the agate balls are separated, and then dried at a temperature of 200°C for 10h, and then sieved through an 80-mesh sieve to obtain a raw material mixture; the mass of the agate balls in the preparation is prepared in a ratio of 10mm:5mm:2mm in diameter = 3:2:1; the mass ratio of the dried initial raw material powder, agate balls and deionized water is 1:2:4;
[0043] S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder;
[0044] The pre-sintering method comprises: heating from room temperature to 800° C. at a heating rate of 8° C. / min, pre-sintering at a constant temperature for 4 hours, and naturally cooling to room temperature to obtain pre-sintered powder;
[0045] S4, add agate balls and deionized water to the pre-burned powder obtained in S3, ball mill at a speed of 800r / min for 2h, separate the agate balls, dry at a temperature of 250°C for 8h, pass through a 100-mesh sieve after grinding, and obtain the pre-burned powder after ball grinding; the mass of the agate balls is in a ratio of 10mm:5mm:2mm=3:2:1 in diameter; the mass ratio of the pre-burned powder, agate balls and deionized water is 1:2:3;
[0046] S5, adding a 3% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body; the mass ratio of the 3% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder is 12%:1;
[0047] S6, sintering the ceramic green body obtained in S5 to obtain a medium-entropy high-temperature giant dielectric ceramic material;
[0048] The sintering method is: heating from room temperature to 500°C at a heating rate of 3°C / min, keeping the temperature for 3 hours, then heating to 1000°C at a heating rate of 3°C / min, sintering at a constant temperature in air for 4 hours, and then cooling to room temperature at a cooling rate of 9°C / min.
[0049] The dielectric constant and dielectric loss of the medium-entropy high-temperature giant dielectric ceramic material prepared in this embodiment are measured, and the measured data are shown in Table 1:
[0050] Table 1 Performance test of Example 1
[0051] frequency <![CDATA[Temperature range where the dielectric constant > 10 5 > Dielectric constant in the corresponding temperature range Dielectric loss in the corresponding temperature range 100Hz 219℃~350℃ >10314 0.1271~0.3810 500Hz 236℃~350℃ >10190 0.2279~0.2622
[0052] like Figure 4 As shown, [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3 medium entropy ceramic material has a dielectric constant of 10 at a frequency of 1 kHz and a temperature above 249°C. 5 The order of magnitude, the loss is less than 0.2, and the high dielectric constant is conducive to the development trend of device miniaturization, integration and portability. The medium-entropy high-temperature giant dielectric ceramic material prepared in this embodiment can be used for the preparation of high-temperature capacitors.
[0053] Example 2
[0054] The composition formula of the medium-entropy high-temperature giant dielectric ceramic material of this embodiment is: 0.95[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.05Bi(MgZr) 0.5 O3.
[0055] This embodiment also provides a method for preparing the above medium-entropy high-temperature giant dielectric ceramic material, which is:
[0056] S1. According to the chemical composition of medium-entropy high-temperature giant dielectric ceramic materials: 0.95[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.05Bi(MgZr) 0.5O3 selecting initial raw material powders and drying them to obtain dried initial raw material powders;
[0057] The selected Na2CO3 raw material powder, Bi2O3 raw material powder, K2CO3 raw material powder and BaCO3 raw material powder are dried at 300°C for 6 hours respectively; the selected TiO2 raw material powder, MgO raw material powder and ZrO2 raw material powder are dried at 900°C for 4 hours;
[0058] The purity of the Na2CO3 raw material is 99.8%, the purity of the Bi2O3 raw material is 99%, the purity of the K2CO3 raw material is 99%, the purity of the BaCO3 raw material is 99%, the purity of the TiO2 raw material is 98%, the purity of the MgO raw material is 99.9%, and the purity of the ZrO2 raw material is 99.9%; S2, the dried Na2CO3 powder, Bi2O3 powder, K2CO3 powder, BaCO3 powder, TiO2 powder, MgO powder and ZrO2 powder in S1 are heated to 0.95[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.05Bi(MgZr) 0.5 The raw material mixture is prepared in a stoichiometric ratio of 100:100 mm:50 mm:2 mm, and agate balls and deionized water are added, and the mixture is ball-milled at a speed of 350 r / min for 10 hours. After the agate balls are separated, the mixture is dried at a temperature of 180°C for 24 hours, and the mixture is sieved through a 100-mesh sieve after grinding to obtain a raw material mixture. The mass of the agate balls in the mixture is prepared in a ratio of 10 mm:5 mm:2 mm in diameter = 4:3:1. The mass ratio of the dried initial raw material powder, agate balls and deionized water is 1:2:3.
[0059] S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder;
[0060] The pre-sintering method comprises: heating from room temperature to 900° C. at a heating rate of 5° C. / min, pre-sintering at a constant temperature for 3 hours, and naturally cooling to room temperature to obtain pre-sintered powder;
[0061] S4, add agate balls and deionized water to the pre-burned powder obtained in S3, ball mill at a speed of 350r / min for 6h, separate the agate balls, dry at a temperature of 180°C for 24h, grind and sieve through a 180-mesh sieve to obtain the pre-burned powder after ball grinding; the mass of the agate balls is in a ratio of 10mm:5mm:2mm=4:3:1 in diameter; the mass ratio of the pre-burned powder, agate balls and deionized water is 1:2:2.5;
[0062] S5, adding a 5% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body; the mass ratio of the 5% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder is 10%:1;
[0063] S6, sintering the ceramic green body obtained in S5 to obtain a medium-entropy high-temperature giant dielectric ceramic material;
[0064] The sintering method is: heating from room temperature to 550°C at a heating rate of 3°C / min, keeping the temperature for 2h, then heating to 1060°C at a heating rate of 5°C / min, sintering at a constant temperature in air for 2h, and then cooling to room temperature at a cooling rate of 8°C / min.
[0065] The medium-entropy high-temperature giant dielectric ceramic material prepared in this embodiment can be used for the preparation of high-temperature capacitors.
[0066] The dielectric constant and dielectric loss of the medium-entropy high-temperature giant dielectric ceramic material prepared in this embodiment were measured, and the measured data are shown in Table 2:
[0067] Table 2 Performance test of Example 2
[0068] frequency <![CDATA[Temperature range with relative permittivity > 10 5 > Dielectric constant in the corresponding temperature range Dielectric loss in the corresponding temperature range 100Hz 83~350℃ >10208 0.2016~0.3223 500Hz 156~350℃ >10129 0.1356~0.2090
[0069] like Figure 5 As shown, the 0.95[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.05Bi(MgZr) 0.5 The dielectric constant of O3 medium entropy ceramic material reaches 10 at a frequency of 1 kHz and a temperature above 166°C. 5 On the other hand, within the temperature range of 166-315°C, the medium-entropy ceramic material exhibits a broadened dielectric peak, which greatly improves the application temperature range of high-temperature capacitors made of medium-entropy high-temperature giant dielectric ceramic materials in this embodiment.
[0070] Example 3
[0071] The composition formula of the high-entropy high-temperature giant dielectric ceramic material of this embodiment is: 0.90[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.10Bi(MgZr) 0.5 O3.
[0072] This embodiment also provides a method for preparing the above-mentioned high-entropy high-temperature giant dielectric ceramic material, which is:
[0073] S1. According to the chemical composition of high entropy high temperature giant dielectric ceramic materials: 0.90[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.10Bi(MgZr) 0.5 O3 selecting initial raw material powders and drying them to obtain dried initial raw material powders;
[0074] The selected Na2CO3 raw material powder, Bi2O3 raw material powder, K2CO3 raw material powder and BaCO3 raw material powder are dried at 300°C for 6 hours respectively; the selected TiO2 raw material powder, MgO raw material powder and ZrO2 raw material powder are dried at 900°C for 4 hours;
[0075] The purity of the Na2CO3 raw material is 99.8%, the purity of the Bi2O3 raw material is 99%, the purity of the K2CO3 raw material is 99%, the purity of the BaCO3 raw material is 99%, the purity of the TiO2 raw material is 98%, the purity of the MgO raw material is 99.9%, and the purity of the ZrO2 raw material is 99.9%;
[0076] S2, the dried Na2CO3 powder, Bi2O3 powder, K2CO3 powder, BaCO3 powder, TiO2 powder, MgO powder and ZrO2 powder in S1 were heated to 0.90[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.10Bi(MgZr) 0.5 The raw material mixture is prepared in a stoichiometric ratio of 10 mm: 5 mm: 2 mm, and agate balls and deionized water are added, and the mixture is ball-milled at a speed of 600 r / min for 4 hours. After the agate balls are separated, the mixture is dried at a temperature of 120° C. for 48 hours, and the mixture is sieved through a 120-mesh sieve after grinding to obtain a raw material mixture; the mass of the agate balls in the mixture is prepared in a ratio of 10 mm: 5 mm: 2 mm in diameter = 4: 3: 1; the mass ratio of the dried initial raw material powder, agate balls and deionized water is 1: 1.5: 2;
[0077] S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder;
[0078] The pre-sintering method comprises: heating from room temperature to 980° C. at a heating rate of 2° C. / min, pre-sintering at a constant temperature for 1 hour, and naturally cooling to room temperature to obtain pre-sintered powder;
[0079] S4, add agate balls and deionized water to the pre-burned powder obtained in S3, ball mill at a speed of 300 / min for 10 hours, separate the agate balls, dry at a temperature of 120°C for 48 hours, and pass through a 230-mesh sieve after grinding to obtain the pre-burned powder after ball grinding; the mass of the agate balls is in a ratio of 10mm:5mm:2mm=4:3:1 in diameter; the mass ratio of the pre-burned powder, agate balls and deionized water is 1:1.5:2;
[0080] S5, adding a polyvinyl alcohol aqueous solution with a mass fraction of 8% to the pre-burned powder after ball grinding obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body; the mass ratio of the polyvinyl alcohol aqueous solution with a mass fraction of 8% to the pre-burned powder after ball grinding is 5%:1;
[0081] S6, sintering the ceramic green body obtained in S5 to obtain a high-entropy high-temperature giant dielectric ceramic material;
[0082] The sintering method is: heating from room temperature to 600°C at a heating rate of 1.5°C / min, keeping the temperature for 1 hour, then heating to 1200°C at a heating rate of 9°C / min, sintering at a constant temperature in air for 1 hour, and then cooling to room temperature at a cooling rate of 5°C / min.
[0083] The high-entropy high-temperature giant dielectric ceramic material prepared in this embodiment can be used for the preparation of high-temperature capacitors.
[0084] The dielectric constant and dielectric loss of the high-entropy high-temperature giant dielectric ceramic material prepared in this embodiment are measured, and the measured data are shown in Table 3:
[0085] Table 3 Performance test of Example 3
[0086]
[0087]
[0088] like Figure 6 As shown, the 0.90[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.10Bi(MgZr) 0.5 The dielectric constant of O3 high entropy ceramic materials is above 5000 at a frequency of 1kHz and a temperature range of 120°C. In the temperature range of 150-350°C, the dielectric constant change is less than 0.67%, and the dielectric constant temperature coefficient is less than 3.06*10 -4 / ℃, showing good temperature stability of the dielectric constant, which greatly improves the stability of the high-temperature capacitor prepared by the high-entropy high-temperature giant dielectric ceramic material of this embodiment.
[0089] Example 4
[0090] The composition formula of the high entropy high temperature giant dielectric ceramic material of this embodiment is: 0.85[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.15Bi(MgZr) 0.5 O3.
[0091] This embodiment also provides a method for preparing the above-mentioned high-entropy high-temperature giant dielectric ceramic material, which is:
[0092] S1. According to the chemical composition of high entropy high temperature giant dielectric ceramic materials: 0.85[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.15Bi(MgZr) 0.5 O3 selecting initial raw material powders and drying them to obtain dried initial raw material powders;
[0093] The selected Na2CO3 raw material powder, Bi2O3 raw material powder, K2CO3 raw material powder and BaCO3 raw material powder are dried at 300°C for 6 hours respectively; the selected TiO2 raw material powder, MgO raw material powder and ZrO2 raw material powder are dried at 900°C for 4 hours;
[0094] The purity of the Na2CO3 raw material is 99.8%, the purity of the Bi2O3 raw material is 99%, the purity of the K2CO3 raw material is 99%, the purity of the BaCO3 raw material is 99%, the purity of the TiO2 raw material is 98%, the purity of the MgO raw material is 99.9%, and the purity of the ZrO2 raw material is 99.9%;
[0095] S2, the dried Na2CO3 powder, Bi2O3 powder, K2CO3 powder, BaCO3 powder, TiO2 powder, MgO powder and ZrO2 powder in S1 were heated to 0.85[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-0.15Bi(MgZr) 0.5The raw material mixture is prepared in a stoichiometric ratio of 100 mm: 50 mm: 20 mm, and 100 meshes are sieved to obtain a raw material mixture; the mass of the agate balls in the preparation is prepared in a ratio of 10 mm: 5 mm: 2 mm in diameter = 3: 3: 1; the mass ratio of the dried initial raw material powder, agate balls and deionized water is 1: 2: 2;
[0096] S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder;
[0097] The pre-sintering method comprises: heating from room temperature to 850° C. at a heating rate of 5° C. / min, pre-sintering at a constant temperature for 2 hours, and naturally cooling to room temperature to obtain pre-sintered powder;
[0098] S4, add agate balls and deionized water to the pre-burned powder obtained in S3, ball mill at a speed of 500r / min for 6h, separate the agate balls, dry at a temperature of 1500°C for 12h, pass through a 100-mesh sieve after grinding, and obtain the pre-burned powder after ball grinding; the mass of the agate balls is in a ratio of 10mm:5mm:2mm=3:3:1 in diameter; the mass ratio of the pre-burned powder, agate balls and deionized water is 1:2:2;
[0099] S5, adding a 5% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body; the mass ratio of the 5% by mass polyvinyl alcohol aqueous solution to the ball-milled pre-burned powder is 8%:1;
[0100] S6, sintering the ceramic green body obtained in S5 to obtain a high-entropy high-temperature giant dielectric ceramic material;
[0101] The sintering method is: heating from room temperature to 550°C at a heating rate of 2°C / min, keeping the temperature for 2h, then heating to 1100°C at a heating rate of 5°C / min, sintering at a constant temperature in air for 2h, and then cooling to room temperature at a cooling rate of 6°C / min.
[0102] The dielectric constant and dielectric loss of the high-entropy high-temperature giant dielectric ceramic material prepared in this embodiment are measured, and the measured data are shown in Table 4:
[0103] Table 4 Performance test of Example 4
[0104] frequency <![CDATA[Temperature range where the dielectric constant > 10 5 > Dielectric constant in the corresponding temperature range Dielectric loss in the corresponding temperature range 100Hz 89~350℃ >10122 0.2507~0.3625 500Hz 130~350℃ >10027 0.1807~0.1835
[0105] like Figure 7 As shown, the 0.85[(Bi 0.5 Na 0.5 ) 0.85 K0.1 Ba 0.1 ]TiO3-0.15Bi(MgZr) 0.5 O3 high entropy ceramic material shows a broadened dielectric peak at 1 kHz frequency and 139-350℃ temperature range, and its dielectric constant reaches 10 5 The order of magnitude, the loss is less than 0.186, showing a certain temperature stability. The high-entropy high-temperature giant dielectric ceramic material prepared in this embodiment can be used for the preparation of high-temperature capacitors.
[0106] Figure 1 The medium and high entropy high temperature giant dielectric (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 Ba 0.1 ]TiO3-xBi(MgZr) 0.5 The entropy value and tolerance factor of O3 ceramic materials are 1.023, 1.018, 1.013 and 1.008, respectively, all within the range of 0.825-1.059, indicating that all ceramic samples have stable structures; and their entropy values are 1.173R, 1.395R, 1.535R and 1.646R, respectively. Obviously, the increase in configurational entropy effectively improves the stability of the thermodynamically unstable structure.
[0107] Figure 2 is the XRD diagram of the medium and high entropy high temperature giant dielectric ceramic materials in Examples 1-4 of the present invention. Figure 2 It can be seen that the ceramic materials prepared in Examples 1 to 4 are all pure perovskite structures. In the range of 2θ=20-80°, all ceramic samples show seven main lattice diffraction peaks unique to the perovskite structure, and no second phase is observed. Usually, the (200) peak near 46.5° splits into a (200) / (002) double peak, indicating that the ceramic sample has a tetragonal phase structure at this time; the (111) peak of the ceramic sample near 40° splits into a (003) / (021) double peak, indicating that the ceramic sample has a rhombohedral phase structure. Obviously, the x≤0.10 component ceramic sample is a coexistence structure of rhombohedral and tetragonal phases; when x=0.15, in addition to the (200) / (002) double peak near 46.5°, the split peak (003) / (021) near 40° merges into a single peak (111) structure, indicating that the ceramic sample is a tetragonal phase structure at this time. It can be seen that the change in configuration entropy effectively reduces the structural distortion of the material and improves the structural stability of the material. At the same time, the trigonal and tetragonal phases with polar structural characteristics help improve the spontaneous polarization and dielectric properties of the material.
[0108] Figure 3It is a SEM scan of the medium and high entropy high temperature giant dielectric ceramic materials in Examples 1-4 of the present invention. Figure 3 It can be seen that the ceramic materials prepared in Examples 1 to 4 have uniform grain size, dense particle distribution, average grain size of 6 to 8 μm, and clear grain boundaries. Usually, high-temperature sintering provides certain reducing conditions, and natural cooling in the later stage of sintering is conducive to the insulation of ceramic grain boundaries. Compared with the insulation of grain boundaries, semiconducting grains and insulating grain boundaries improve the dielectric properties of ceramic materials. Further, in this example, donor doping and acceptor doping are carried out simultaneously, which is simple in process, short in production cycle, energy-saving and low in cost.
[0109] The medium and high entropy high temperature giant dielectric ceramic material composition formula (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 In O3, it can also be: 0≤x<0.2, A is any one of Ba, Sr, Ca, B1 B2 is any one of Mg, Zn, Fe and any one of Zr, Hf, Sn in combination, all of which can be prepared into medium- and high-entropy high-temperature giant dielectric ceramic materials for high-temperature capacitors.
[0110] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A medium- and high-entropy high-temperature giant dielectric ceramic material, characterized in that: The composition formula of the medium and high entropy high temperature giant dielectric ceramic material is: (1-x)[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 O3; Among them: 0≤x≤0.15, A is Ba, B1 is Mg, and B2 is Zr.
2. A method for preparing the medium- and high-entropy high-temperature giant dielectric ceramic material as claimed in claim 1, characterized in that: The method is: S1. According to the chemical composition of medium and high entropy high temperature giant dielectric ceramic materials (1-x) [(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 O3 selecting initial raw material powders and drying them to obtain dried initial raw material powders; S2, the dried initial raw material powder obtained in S1 is treated according to (1-x)[(Bi 0.5 Na 0.5 ) 0.85 K 0.1 A 0.1 ]TiO3-xBi(B1B2) 0.5 The raw materials are mixed in a stoichiometric ratio of 1,2-dihydrogen 2-nitrogen (2-nitrogen) and 1,4-dihydrogen 2-nitrogen (2-nitrogen) (2-nitrogen) (3-nitrogen) (4-nitrogen) (5-nitrogen) (6-nitrogen) (7-nitrogen) (8-nitrogen) (9-nitrogen) (10-100-110-120-130-140-260-280-300-360-38 ... S3, pre-calcining the raw material mixture obtained in S2 in air to obtain pre-calcined powder; The pre-sintering method comprises: heating from room temperature to 800°C to 980°C at a heating rate of 2°C / min to 8°C / min, pre-sintering at a constant temperature for 1h to 4h, and naturally cooling to room temperature to obtain pre-sintered powder; S4, adding agate balls and deionized water to the pre-burned powder obtained in S3, ball milling at a speed of 300r / min-800r / min for 2h-10h, separating the agate balls, drying at a temperature of 120°C-250°C for 8h-48h, and passing through a 100-mesh sieve to a 230-mesh sieve after grinding to obtain a pre-burned powder after ball milling; S5, adding a polyvinyl alcohol aqueous solution with a mass fraction of 3% to 8% to the pre-sintered powder after ball grinding obtained in S4, grinding, passing through a 40-mesh sieve, and tableting to obtain a ceramic green body; S6. Sintering the ceramic green body obtained in S5 to obtain medium- and high-entropy high-temperature giant dielectric ceramic materials.
3. The method according to claim 2, characterized in that The raw material powders containing K and Na in the initial raw material powders in S1 are carbonates corresponding to the elements, the raw material powders containing A are carbonates corresponding to the elements, and the raw material powders containing Bi, Ti, B1, and B2 are oxides corresponding to the elements.
4. The method according to claim 2, characterized in that: The mass of the agate balls in the ingredients described in S2 is in the ratio of diameter 10mm:5mm:2mm=(3-4):(2-3):1; the mass ratio of the dried initial raw material powder, agate balls and deionized water is 1:(1.5-2):(2-4).
5. The method according to claim 2, characterized in that: The mass of the agate balls in S4 is in the ratio of diameter 10mm:5mm:2mm=(3-4):(2-3):1; the mass ratio of the pre-burned powder, agate balls and deionized water is 1:(1.5-2):(2-3).
6. The method according to claim 2, characterized in that The tabletting method described in S5 is: maintaining the pressure for 10s to 60s under a unidirectional pressure condition of 100MPa to 350MPa.
7. The method according to claim 2, characterized in that The mass ratio of the polyvinyl alcohol aqueous solution with a mass fraction of 3% to 8% in S5 to the pre-sintered powder after ball grinding is (5% to 12%):
1.
8. The method according to claim 2, characterized in that: The sintering method described in S6 is: heating from room temperature to 500°C to 600°C at a heating rate of 1.5°C / min to 3°C / min, keeping warm for 1h to 3h, then heating to 1000°C to 1200°C at a heating rate of 3°C / min to 9°C / min, sintering at a constant temperature in air for 1h to 4h, and then cooling to room temperature at a cooling rate of 5°C / min to 9°C / min.
9. The method according to claim 2, characterized in that: The medium and high entropy high temperature giant dielectric ceramic materials described in S6 have a dielectric constant > 10 in the temperature range of 89°C to 350°C and the frequency range of 100Hz to 500Hz. 5 .
10. An application of medium- and high-entropy high-temperature giant dielectric ceramic materials prepared by the method according to any one of claims 1 to 9, characterized in that: The medium and high entropy high temperature giant dielectric ceramic materials are used for preparing high temperature capacitors.
Citation Information
Patent Citations
Lanthanum substituted titanate copper bismuth sodium giant dielectric ceramic material and preparation method thereof
CN102219508A
High-entropy perovskite oxide doped ceramic, preparation method and application thereof
CN115991599A
Sodium bismuth titanate-based lead-free antiferroelectric ceramic material and preparation method thereof
CN116120053A
High-temperature stable high-entropy ceramic material with excellent energy storage performance and preparation method of high-temperature stable high-entropy ceramic material
CN118878319A
Bismuth-based Complex Perovskite Lead-free Piezoelectric Ceramics and Manufacturing Method therefor
KR1020120134928A